Adenosine‐guided radiofrequency catheter ablation of atrial fibrillation: A meta‐analysis of randomized control trials. Issue 4 (28th March 2017) - Letsas, Konstantinos P.; Georgopoulos, Stamatis; Efremidis, Michael; Liu, Tong; Bazoukis, George; Vlachos, Konstantinos; Karamichalakis, Nikolaos; Lioni, Louiza; Sideris, Antonios; Ehrlich, Joachim R.
Abstract: Background: The prognostic significance of adenosine‐mediated dormant pulmonary vein conduction, and whether such dormant conduction should be eliminated, remains controversial. We sought to perform a meta‐analysis of data from eligible studies to delineate the prognostic impact of adenosine‐guided radiofrequency catheter ablation of atrial fibrillation. Methods: A systematic literature search was performed using online databases in order to identify relevant studies from January 2004 to September 2016. Ten studies [six observational and four randomized control trials (RCTs)] were included in the analysis. Results: Five studies (two observational and three RCTs) compared the efficacy of adenosine‐mediated elimination of dormant conduction versus no adenosine test. Overall, the adenosine‐guided ablation strategy displayed better long‐term outcomes as compared with no adenosine testing (RR 1.08, 95% CI 1.01–1.14, p =0.02; Heterogeneity: I 2 =42%, p : 0.14). The meta‐analysis of only RCTs failed to show any differences between the two strategies (RR 1.03, 95% CI 0.96–1.11, p =0.37; Heterogeneity: I 2 0%, p : 0.41). Eight studies (five observational and three RCTs) addressed the efficacy of adenosine‐induced dormant conduction and additional ablation versus no dormant conduction during adenosine challenge. Overall, a trend towards a better outcome in those without dormant conduction during drug challenge was noted (RR 0.89, 95% CI 0.77–1.03, p =0.11; Heterogeneity: I 2 65% p : 0.006). The pooled analysis of RCTs failed to show any differences between the two arms (RR 0.90, 95% CI 0.62–1.30, p = 0.57; Heterogeneity: I 2 88%, p : 0.0002). Conclusions: Adenosine‐guided radiofrequency catheter ablation of atrial fibrillation does not provide additional benefit in terms of freedom of arrhythmia recurrence.